How competent are cat owners in caring for their cats? - İbrahim ŞEKER; Ömer ERTEN; Abdurrahman KÖSEMAN; Şenol KOŞAN (Revista MVZ Cordoba)
Objective. This study was conducted to determine the perceptions of cat owners in Türkiye regarding the welfare conditions of their cats and their attitudes and knowledge levels during the care of their cats. Materials and methods. The research material consists of data obtained from questionnaires conducted with 494 cat owners. Results. Among cat owners, 98.6% kept cat food in closed boxes and 93.5% took precautions to prevent their cats from accessing household chemicals. In this study, according to the answers given by the participants to the questionnaire questions, statistically significant differences were found between the options in terms of their answers to all other questions, except for the answers given by the cat owners to the questions of whether they use nets for their cats on the windows and/or balconies of their houses and the frequency of changing the litter of their cats (p<0.01). Conclusions. It was determined that the majority of cat owners were generally correct and adequate in terms of their attitudes and knowledge levels during the care of their cats. However, it has been determined that cat owners do not have sufficient and correct information and preferences about using nets for their cats for protective purposes in the windows and balconies of their houses, giving their cats additional foods such as sausage, salami, sausage.